Scenography as a Key Element in Theatrical Performance: Taking the Theatrical Performance "Immigrants" as an Example (Raparin Journal of Humanities (RJH), 2025)
This research discusses all the elements that appear on the stage in a theatrical production، known as "scenography." It encompasses everything the audience sees or hears during the performance، such as set design، lighting، and sound. The issue is that many researchers or theater critics often focus on acting، directing، and storytelling، giving little attention to scenography، treating it as secondary. However، the importance of this study lies in demonstrating that scenography is not merely for aesthetic appeal. On the contrary، it plays a crucial role in helping the audience grasp the message، meaning، and emotional depth of a performance. The main goal of this research is to clarify the significance of scenography. To illustrate this، the study examines the play Migrants as a case study. It explores how scenography—through the use of a dark underground setting، sound effects، props، color، and lighting—effectively conveys the suffering and despair of migrants، immersing the audience in the play’s themes even without spoken dialogue. Ultimately، the research concludes that scenography in theater، particularly in Migrants، is essential and cannot be separated from a successful theatrical production that aims to convey deep human messages.